Antithrombotic therapy in cancer patients with cardiovascular diseases: daily practice recommendations by the Hemostasis Working Party of the German Society of Hematology and Medical Oncology (DGHO) and the Society for Thrombosis and Hemostasis Research (GTH e.V.) - Parmentier, Stefani Barbara; Koschmieder, Steffen; Henze, Larissa; Griesshammer, Martin; Matzdorff, Axel; Bakchoul, Tamam; Langer, Florian; Alesci, Rosa Sonja; Dürschmied, Daniel; Thomalla, Goetz; Riess, Hanno (Hämostaseologie, 2024)
Active cancer by itself but also chemotherapy is associated with an increased risk of cardiovascular disease (CVD) and especially coronary artery disease (CAD) and atrial fibrillation (AF). The frequency of CVD, CAD, and AF varies depending on comorbidities (particularly in older patients), cancer type, and stage, as well as the anticancer therapeutic being taken. Many reports exist for anticancer drugs being associated with CVD, CAD, and AF, but robust data are often lacking. Because of this, each patient needs an individual structured approach concerning thromboembolic and bleeding risk, drug-drug interactions, as well as patient preferences to evaluate the need for anticoagulation therapy and targeting optimal symptom control. Interruption of specific cancer therapy should be avoided to reduce the potential risk of cancer progression. Nevertheless, additional factors like thrombocytopenia and anticoagulation in the elderly and frail patient with cancer cause additional challenges which need to be addressed in daily clinical management. Therefore, the aim of these recommendations is to summarize the available scientific data on antithrombotic therapy (both antiplatelet and anticoagulant therapy) in cancer patients with CVD and in cases of missing data providing guidance for optimal careful decision-making in daily routine.